2014
DOI: 10.2139/ssrn.2471528
|View full text |Cite
|
Sign up to set email alerts
|

Slow Decay of Impact in Equity Markets

Abstract: Using a proprietary dataset of meta-orders and prediction signals, and assuming a quasi-linear impact model, we deconvolve market impact from past correlated trades and a predictable return component to elicit the temporal dependence of the market impact of a single daily meta-order, over a ten day horizon in various equity markets. We find that the impact of single meta-orders is to a first approximation universal and slowly decays to zero (or to a small value), possibly as a power-law. We show that auto-corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 27 publications
(31 reference statements)
6
43
0
Order By: Relevance
“…Further studies have shown that impact is to a large part transient: after execution the price falls from its peak to some intermediate level, that some studies (Bershova and Rakhlin 2013, Gomes and Waelbroeck 2015, Moro et al 2009) argue to be close to 2/3 of the peak impact, in agreement with equilibrium models (Farmer et al 2013). In Brokmann et al (2014) the authors find that this high permanent level may be due to the correlation between the trader's execution decision and the residual order flow 2 and to the price signal that triggered the decision to trade: By taking into account these effects they argue that the "bare" permanent impact (or mechanical permanent impact) is much lower and possibly even zero. Finally, Gomes and Waelbroeck (2015) conduct a separate impact study of informed trades and cash-flow (uninformed) trades, to find that the latter have no permanent effect on the price (although the transient impact are similar for both types of trades).…”
Section: Comparison With Related Literaturementioning
confidence: 99%
“…Further studies have shown that impact is to a large part transient: after execution the price falls from its peak to some intermediate level, that some studies (Bershova and Rakhlin 2013, Gomes and Waelbroeck 2015, Moro et al 2009) argue to be close to 2/3 of the peak impact, in agreement with equilibrium models (Farmer et al 2013). In Brokmann et al (2014) the authors find that this high permanent level may be due to the correlation between the trader's execution decision and the residual order flow 2 and to the price signal that triggered the decision to trade: By taking into account these effects they argue that the "bare" permanent impact (or mechanical permanent impact) is much lower and possibly even zero. Finally, Gomes and Waelbroeck (2015) conduct a separate impact study of informed trades and cash-flow (uninformed) trades, to find that the latter have no permanent effect on the price (although the transient impact are similar for both types of trades).…”
Section: Comparison With Related Literaturementioning
confidence: 99%
“…The obtained model can then be used in an optimal trading scheme (see [Almgren et al, 2005a], [Gatheral, 2010] and [Lehalle and Dang, 2010] and for link with optimal trading see [Almgren and Chriss, 2000], [Gatheral and Schied, 2012] and [Bouchard et al, 2011]), or used by an investment firm to understand its trading costs (like in [Engle et al, 2012], [Bershova and Rakhlin, 2013], [Brokmann et al, 2014] or [Mastromatteo et al, 2013] written by author involved in investment firms).…”
Section: Selection Of the Explanatory Variablesmentioning
confidence: 99%
“…The purpose of the econophysicist is to understand the behaviour of these two forces and to find the law at the root of the impact of buying/selling pressure on prices' dynamic. See [Gabaix et al, 2006], and [Brokmann et al, 2014].…”
Section: Positioningmentioning
confidence: 99%
See 2 more Smart Citations